Strategi Pedagang Pasar Tradisional Menghadapi Persaingan Dengan Retail Modern Di Kota Mojokerto - Eny Setyariningsih; Budi Utami (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2021)
Along with the development of the times to meet the needs of the community, modern retail is formed that prioritizes the convenience of buyers by carrying out several strategies. The rapid development of modern markets compared to traditional markets in big cities has led to the emergence of various alternatives for people to choose where to shop. Competition between traditional and modern markets provides an advantage for potential consumers because they have more choices of places to shop. This study aims to determine the impact of the existence of modern retail on traditional markets in Mojokerto City. The sample of this research is traditional market traders in Mojokerto City. This research was conducted by observation, interviews, and documentation directly with traditional traders and actors ritail in Mojokerto. Data analysis used qualitative data analysis. The results of the interview show that the impact of the existence of Modern retail on the City of Mojokerto includes a decrease in sales turnover, a decrease in the number of buyers, increased competition between traders. Alternative solutions masala h , the traditional market perform low pricing strategy in order to increase sales can be achieved, Doing service strategy can be sent to areas close groceries , also pursuing a strategy of product quality is not inferior to the products sold by the modern market.